2022
DOI: 10.1177/10732748221084198
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Omani Colorectal Cancer Survivors

Abstract: Background Colorectal cancer (CRC) patients often experience physical and psychological symptoms which affect quality of life (QOL). Purpose This study aimed to identify factors affecting QOL among adult Omani CRC survivors. Methods A prospective cross-sectional study of 124 adult CRC survivors was conducted at the two main oncology referral hospitals in Oman. A validated Arabic version of the European Organisation for Research and Treatment of Cancer-Quality of Life Questionnaire for Colorectal Cancer-29 (EOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…What is more important is not the raw rates of sexual dysfunction but rather the impact that sexual dysfunction is having on those patients. For example, a study of CRC survivors published in 2022 found that older patients were less interested in sex compared with younger patients and complained of less overall sexual dysfunction 40 . Another reported that despite the rates of sexual dysfunction in older men being higher, younger men were more likely to be distressed by sexual disinterest 41 .…”
Section: Discussionmentioning
confidence: 99%
“…What is more important is not the raw rates of sexual dysfunction but rather the impact that sexual dysfunction is having on those patients. For example, a study of CRC survivors published in 2022 found that older patients were less interested in sex compared with younger patients and complained of less overall sexual dysfunction 40 . Another reported that despite the rates of sexual dysfunction in older men being higher, younger men were more likely to be distressed by sexual disinterest 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study displayed that comorbidities and age were factors associated with QOL improvement. Indeed, patients in this study with more comorbidities were more likely to complain of symptoms such as fatigue, pain, constipation, and diarrhea compared to patients without comorbidities and those who were under 60 years of age (Al-Shandudi et al, 2022). The abovementioned findings suggest that age closely relates to QOL improvement.…”
Section: Discussionmentioning
confidence: 53%
“…There were 32 studies exploring gender differences in patients’ psychological outcomes (detailed content shown in Table 1 ). In general, female patients reported worse anxiety (at least 6 months of survival left) [ 11 , 21 , 23 ], depression (at least 1 month after treatment, or within 3.5 to 5 years after diagnosis) [ 21 , 29 , 41 ], body image distress (within 5 years after diagnosis, undergoing chemotherapy treatment, after treatment, or at least 6 months of survival left) [ 12 , 20 , 23 , 40 , 51 ], distress (at 3 months after treatment) [ 32 ], fear of cancer recurrence (within 6 to 36 months after treatment) [ 43 ], emotional functioning (at least 3 months of survival left) [ 35 ], psychological functioning [ 44 ], and mental health (within 1 month after diagnosis) [ 47 ] than male patients. This gender tendency of anxiety, depression, and distress remained at follow-up periods from 6 months to 55 months [ 31 , 49 , 53 ].…”
Section: Resultsmentioning
confidence: 99%